An Analysis of Balinese Swearwords of English Private Course Students in Buleleng Regency - Wisudayanti, Kadek Heni Oktarina (The Art of Teaching English as a Foreign Language (TATEFL), 2020)
This study is intended to find out and analyze on the Balinese swearwords that often used by the English private course students in Buleleng in their daily conversation. Due to the problems discussed, the theories suggested in this research include language definition, sociolinguistics and swearwords definition. The method applied in this research is descriptive qualitative in nature and the data are from the English private course students in Buleleng. The subjects of this research are five English course students that originally came from Buleleng and they also lived in Buleleng. Then, the data analysis is performed to search the kinds of swearwords that they used, the reason of Buleleng people using the swearwords and also how often they speak the swearwords. This study use the swearwords classification according to types of swearwords which stated by Hughes (1998). This study finds the swearwords at several term included word related to religious (pirata), word related to sex (naskleng), word from excrement (tai and bangkaan), word from name of animal (cicing and bojog), and word from mental illness (lengeh,and buduh). Altough those words are dirty or rude to be said, but it often used by the Buleleng people even from the children until the adult. It will still like that for the next many years, because that is their culture herritage from many years ago.